ETNOGRAFI DAN ETNOMETODOLOGI SEBAGAI PENDEKATAN SOSIOLINGUISTIK - Agus Supriyadi (Universitas Khairun, 2022)
Sociolinguistics can develop with the application of ethnographic and ethno methodological approaches. The ethnographic approach is one of the social studies that examines and attempts to explain the rules, cultural norms, values, communicative competence, and linguistic competence related to the use of language as a social setting in a particular society. The ethno methodological approach is an approach that seeks to find the classifications and systems used by the community in making an understanding of the socio-cultural system of the community with a research focus on the phenomenon of everyday language use so that it is known that there is diversity in speech styles. These two types also developed along with the development of linguistics, namely with the birth of communicative ethnography, linguistic ethnography, and conversational analysis.